Editorial Vol.3 (Shanti Journal, 2023)
It is our great pleasure to welcome you all in this third issue of Shanti journal. Shanti Journal: A Multidisciplinary Journal is a bi-annual research platform published by Bishwa Shanti Chiran Milan Campus, Bansbari, and Kathmandu, Nepal. It publishes articles in a wide range of disciplines in arts and humanities, including but not limited to language, literature, culture, international relation, performance arts, media and communication.All submitted articles should report original, previously unpublished research results, empirical or theoretical work, and case studies. The articles submitted to the journal must not be under consideration for publication elsewhere. All submission to this journal will undergo a peer review process, and accepted manuscripts will be published as per journal formats.The Shanti journal actively encourages academic writing and publication across a wide range of specializations in the academic and research domains as part of its mission to achieve excellence. Its broad focus encompasses a wide range of topics, including gender studies, children's rights, media, social and cultural sustainability, and both domestic and global issues. It also includes topics like education, health risks, environmental management, and literature.We genuinely appreciate each and every author for their insightful work. We value the thoughtful contributions made by our distinguished reviewers as well as their support of the Editorial Team during the review procedure.